2008
DOI: 10.1080/15287390701613330
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure of Rana pipiens Tadpoles to UVB Radiation and the Estrogenic Chemical 4- tert -octylphenol

Abstract: While adverse effects of exposure to ultraviolet B radiation (UVBR) and environmental pollutants on amphibians have been documented, few studies examined the effects of interactions between environmental stressors on amphibian health. Here the impacts of chronic exposure to UVBR and the estrogenic chemical 4-tert-octylphenol (OP), alone and in combination, on the survival, development, growth, and metamorphosis of Rana pipiens (northern leopard frog) tadpoles are evaluated. Tadpoles were exposed to environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
1
25
2
Order By: Relevance
“…Whether sublethal UVR effects similarly reduce fitness and contribute to reduced recruitment is less well known, but seems probable. Croteau et al [58] demonstrated that UVR-induced spinal curvature in tadpoles ultimately causes them to starve to death because their swimming ability is compromised and thus are unable to forage. UVR-induced malformations of the eyes and limbs may also negatively affect foraging ability, predator evasion, and reproductive success, but these possibilities have not been tested directly.…”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether sublethal UVR effects similarly reduce fitness and contribute to reduced recruitment is less well known, but seems probable. Croteau et al [58] demonstrated that UVR-induced spinal curvature in tadpoles ultimately causes them to starve to death because their swimming ability is compromised and thus are unable to forage. UVR-induced malformations of the eyes and limbs may also negatively affect foraging ability, predator evasion, and reproductive success, but these possibilities have not been tested directly.…”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
“…Only two studies that we know of have used predation trials to determine that exposure to increased UVR increases the susceptibility of tadpoles to predation [66,67]. Romansic et al [67] attributed this increased susceptibility to predation to UVR-induced tail deformities that may have impaired tadpole swimming Xenopus laevis Artificial lamps [196] Limb and digit malformations Hypsiboas pulchellus Artificial lamps [69] Lithobates pipiens Ambient sunlight [185,186] Artificial lamps [58,200] Rana temporaria Artificial lamps [63] Jaw malformations Hypsiboas pulchellus Artificial lamps [69] Locomotion performance…”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
See 2 more Smart Citations
“…their fitness). One study that has done so demonstrated that UV-B-induced spinal curvature in tadpoles can ultimately lead to death by causing them to swim in circles and thus preventing them from foraging [11]. Similarly, other UV-B-induced malformations and abnormalities such as oedema or bloating [21,22], eye abnormalities [23,24] and hindlimb malformations [12] may also negatively affect foraging ability, predator evasion and reproductive success, but, critically, these possibilities have not been tested directly.…”
Section: Introductionmentioning
confidence: 99%